MOTIVASI KERJA DAN KOMUNIKASI DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PLASA TELKOM TEUKU UMAR DENPASAR - Ni Made Gunastri; Ni Putu Rianasari (Forum Manajemen, 2019)
This research is aimed at finding out any positive influences partially or simultaneously the impact of work motivation and communication upon staff performance at Plaza Telkom Teuku Umar Denpasar. In conducting the analysis based on the set goals, the numbers of respondents are 30 staff at Plaza Telkom Teuku Umar Denpasar, in which questionnaires and likert scale had been applied to collect the data. In addition data analyzing method used was the multiple linear regression analysis, the result of hypothesis showed that variable of work motivation and communication partially had brought a positive and significant impact on staff performance. Next, simultaneously work motivation and communication had also a significant impact on the staff performance at Plaza Telkom Teuku Umar Denpasar.